Emerging trends in the appliance of ultrasonic technology for valorization of agricultural residue into versatile products - Sabaruddin, Fatimah Athiyah; Megashah, Liana Noor; Shazleen, Siti Shazra; Ariffin, Hidayah (Elsevier, 2023)
The utilization of agricultural residues to obtain biocompounds of high-added value has significantly increased in the past decades. The conversion of agro-based residues into valuable products appears to be an economically efficient, environment-friendly, and protracted waste management practice. The implementation of ultrasonic technologies in the conversion of value-added goods from agricultural waste materials through pre-treatment and valorization processes has imparted many advantageous effects including rapid processing, effective process performance, minimization of processing steps, minimal dependency on harmful chemicals, and an increased yield and properties of bio-products. To further enliven the literature and inspire new research investigations, this review covers the comprehensive work including theoretical principles, processes, and potential benefits of ultrasonic treatment technologies to assist the production of bio-products which emphasize the extraction yield and the characteristic of the end-product extracted from agriculture residues. A detailed evaluation of these methods and key aspects impacting their performance as well as the features and shortcomings of each ultrasound-assisted approach is also discussed. This review also addressed some of the challenges associated with using ultrasonic irradiation and proposed several potential techniques to maximize productivity. Understanding the concept of ultrasonication technique allow the academician and industrial practitioners to explore the possibility of applying a greener and sustainable approach of biomass extraction to be translated into higher scale production of commercial products.